2003
DOI: 10.1046/j.1440-1789.2003.00506.x
|View full text |Cite
|
Sign up to set email alerts
|

Subcortical hematoma caused by cerebral amyloid angiopathy: Does the first evidence of hemorrhage occur in the subarachnoid space?

Abstract: Six autopsy cases of subcortical hematoma caused by CAA were examined to elucidate the primary site of hemorrhage. Immunohistochemistry for amyloid beta-protein (A beta) revealed extensive CAA in the intrasulcal meningeal vessels rather than in the cerebral cortical vessels. All of the examined cases had multiple hematomas in the subarachnoid space, mainly in the cerebral sulci, as well as intracerebral hematomas. Each intracerebral hematoma was connected to the subarachnoid hematomas at the depth of cerebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 16 publications
(31 reference statements)
2
58
0
2
Order By: Relevance
“…This has also been suggested in cases of familial leptomeningeal amyloidosis. 8,9 A neuropathologic study by Takeda et al 10 further supports this hypothesis, as it shows that in some cases of CAA the primary hemorrhage occurs in the subarachnoid space.…”
Section: Discussionmentioning
confidence: 82%
“…This has also been suggested in cases of familial leptomeningeal amyloidosis. 8,9 A neuropathologic study by Takeda et al 10 further supports this hypothesis, as it shows that in some cases of CAA the primary hemorrhage occurs in the subarachnoid space.…”
Section: Discussionmentioning
confidence: 82%
“…A small neuropathologic series of 6 autopsy cases of subcortical hematoma caused by CAA showed that at least in some cases the primary hemorrhage appeared to originate from the subarachnoid space. 22 Further prospective studies are urgently required to determine the risk of future intracranial bleeding associated with cSS in CAA.…”
Section: Resultsmentioning
confidence: 99%
“…30 Indeed, a neuropathologic series of 6 autopsy cases of subcortical hematoma caused by CAA showed that multiple leptomeningeal arteries can rupture into the subarachnoid space and the brain parenchyma. 30 This hypothesis is supported by the observation that symptomatic ICH has been noted at (or close to) the site of previous siderosis, 15 although we found that ICH only occurred at the site of cSS in 50% of cases. We found the highest ICH risk in patients with disseminated cSS, which may indicate widespread and numerous leptomeningeal vessels damaged by advanced CAA, providing multiple potential initiation sites for future ICH, increasing the probability of this outcome.…”
Section: Resultsmentioning
confidence: 99%